The franchising relationship quality: Is it important? - Ishak, Khairol Anuar; Jantan, Muhamad (2010)
The concept of relationship quality (RQ) evolved from relational marketing theory, and it provided the impetus for a paradigm shift from transactional relationships to more cooperative and service-centered relationships in business-to-business (B2B) processes. While RQ is a major trend in business management, considerable confusion and disagreement persist regarding what constitute the dimensions, outcomes and impacts of RQ. This paper looks at RQ from the perspectives of B2B, particularly in franchising. A meta-analysis of the literature on the subject is undertaken to ascertain how RQ has been conceptualized, in terms of its dimensions, and impact on business performance.